THE IMPACT OF TURKİSH DEFENCE CLUSTERS ON FİRMS:AN EXAMPLE OF ANKARA PROVİNCE (Third Sector Social Economic Review, 2023)
Globalization, emerging with as a result of technologic improvements trade barriers have started to disappear.This circumstance has enabled to reach both national and international market areas as well as it led to the anticipation that regional industrial agglomerations would lose its importance. Yet, in contrast to expectations domestic and regional dynamics have gained much significance also it has been occurred the policy of clustering. The achivement of clustering policy assert that competitiveness in the global market depends on local dynamics has led to the utilization of these policies in strategically important sectors such as the defense industry. It is possible to see similar examples of defense industry clusters, of which there are various examples around the world, in Turkey. There are some defence industry clusters in the first instance Ankara, Istanbul, Izmir and Eskisehir. The research, aimed to determine the impact of defence industry clusters on firms was utilised case study pattern, one of qualitative methods. Within the scope of the study 20 companies, located in Ankara, that are members of the OSTİM Defense and Aviation Cluster (OSSA) and Teknokent Defense Industry Cluster (TSSK) were interwieved. It was utilised semi- structured form, prepared by expert opinions in the interviews. Data obtained with as a result of interviews were analyzed via content analysis method. As a result of the content analysis based on the research data, the opinions of the participants on the impact of defense industry clusters on firms and the frequency of their expression are grouped under four main headings
Keywords: Cluster; Defence Industry; Defence Industry Clusters; Regional Development; Geography